Bioinspired Materials for Water Purification - Gonzalez-Perez, Alfredo (Materials (Basel), 2016)
Water scarcity issues associated with inadequate access to clean water and sanitation is a ubiquitous problem occurring globally. Addressing future challenges will require a combination of new technological development in water purification and environmental remediation technology with suitable conservation policies. In this scenario, new bioinspired materials will play a pivotal role in the development of more efficient and environmentally friendly solutions. The role of amphiphilic self-assembly on the fabrication of new biomimetic membranes for membrane separation like reverse osmosis is emphasized. Mesoporous support materials for semiconductor growth in the photocatalytic degradation of pollutants and new carriers for immobilization of bacteria in bioreactors are used in the removal and processing of different kind of water pollutants like heavy metals. Obstacles to improve and optimize the fabrication as well as a better understanding of their performance in small-scale and pilot purification systems need to be addressed. However, it is expected that these new biomimetic materials will find their way into the current water purification technologies to improve their purification/removal performance in a cost-effective and environmentally friendly way.